The Multiple Intelligence Based Enrichment Module on the Development of Human Potential: Examining its Impact and the Views of Teachers (Malaysian Journal of Learning and Instruction, 2016)
Purpose â€“ Howard Gardnersâ€™ concept of multiple intelligence (MI) offers an alternative perspective on intelligence which highlights the importance of acknowledging learner diversity, individual talents and the development of human potentials. MI has been used as a basis for the construction of modular enrichment activities to facilitate the development of human potential among boarding school students. This study examines (1) the effects of such activities on students of different multiple intelligence profiles and (2) the teachersâ€™ views of the MI based module and activities. Methodology â€“ The study employs a quasi-experimental design with pre- and post-tests administered before and after treatment of the modular enrichment activities. Two groups of students from two Mara Junior Science Colleges (MRSM) in Malaysia participated in the study as the control and treatment groups. McKenzieâ€™s multiple intelligences instrument was used as the pre- and post-test measure. A semi-structured interview protocol was used to obtain teachersâ€™ views of the enrichment activities. Findings â€“ The study found that the MI post-test was favourable towards the treatment group. Students in the treatment group improved on each multiple intelligence profile compared with students in the control group. The qualitative analysis of the interview data revealed favourable responses from the teachers towards the modular enrichment activities and the inclusion of MI. Significance â€“ This study highlights the importance of recognising that each student has his/her distinct potential. These differences can be captured through the construction of various enrichment activities that emphasise on the different multiple intelligences. The modular learning experience simplifies the process of teaching and learning. It enables students and teachers to understand the objectives to be achieved through diverse problem solving and creative production activities. It is hoped that through this study, educators and teachers will gain ideas about ways in which a MI perspective can help them to tap student potential.